Effects of Dietary Carbohydrate Profile on Nocturnal Metabolism, Sleep, and Wellbeing: A Review - Mantantzis, Konstantinos; Campos, Vanessa; Darimont, Christian; Martin, Francois-Pierre (Frontiers in Public Health, 2022)
Sleep is a crucial biological function and a well-established driver of health and well-being across the lifespan. In this review, we describe how sleep in humans is associated with specific circadian metabolic and physiological changes, and how the organization of sleep-wake states is related to regulation of nocturnal metabolism during fasting. Among the modifiable factors that can contribute to sleep-related benefits, emerging evidence suggests that diet and nocturnal changes in glucose regulation are strong determinants of sleep quality. Here, we review studies that have explored the importance of quantity and quality of dietary carbohydrates and proteins in modulation of sleep and sleep-related health benefits. Future research may guide the creation of nutritional solutions to improve sleep, which could lead to positive changes in health, well-being, and overall quality of life.